Regular expression patterns for trust attributes in E-Commerce website - Muhammad Rushdi Rusli, 1984-, author; Ab. Razak Che Hussin, author; Halim Mohamed Dahlan, author; International Conference on Research and Innovation in Information Systems (2009 : Johor) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL